Transformasi Permasalahan Limbah Kotoran Sapi ke dalam Aspek Desain - Rahardiani, Amira; Nugraha, Adhi; Malasan, Prananda Luffiansyah; Taepoer, Raditya Ardianto (Aliansi Desainer Produk Industri Indonesia (ADPII), 2024)
Globally, environmental pollution stemming from livestock waste remains a widespread and unresolved concern. The contamination resulting from such waste can have adverse effects on both air and water quality, impacting not only livestock owners but also neighboring non-farming communities. This paper focuses specifically on the case study of cow dung waste accumulation in the local ditches of a Cattle Farmers' village in West Java called Bukatanah Village to discuss socio-environmental concerns. Our ongoing research closely aligns with exploring the potential of residents in Bukatanah Village to address the environmental issues prevalent in their living areas. Moreover, this paper is dedicated to illustrating the significance of co-designing the concept in collaboration with the local community rather than imposing a top-down approach in the village. The process is shaped by a series of design ethnography observations, participatory design workshops, material exploration, and project evaluation stages. This paper illustrates a rethinking of solving environmental problems by engaging the locals in